2011
DOI: 10.1007/s10342-011-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

Site and stand characteristics related to surface erosion occurrence in forests of Catalonia (Spain)

Abstract: This study aims at identifying forest areas affected by surface erosion in Catalonia. It analyses the characteristics of forests that are related to erosion occurrence. The data on erosion observations and stand variables were obtained from the Third Spanish National Forest Inventory (2000)(2001). We used the classification tree method to study the presence-absence of surface erosion in four different forest types, pure coniferous, pure broadleaf and mixed stands as well in forested semiarid areas. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
17
1
1
Order By: Relevance
“…timber production and watershed protection (Price et al 2011). Analyzing the effect of forest site and stand characteristics on soil erosion can help recognize forests susceptible to erosion and determine management practices that can enhance soil protection (Selkimäki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…timber production and watershed protection (Price et al 2011). Analyzing the effect of forest site and stand characteristics on soil erosion can help recognize forests susceptible to erosion and determine management practices that can enhance soil protection (Selkimäki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Forest information used for land degradation processes is usually defined by variables such as canopy cover, often feed into already predefined empirical models such as RUSLE (Zhou et al, 2008;Mohammad & Adam, 2010;Jamshidi et al, 2013) or expert models (Lavado Contador et al, 2009) used for estimating the vulnerability of sites. There are also few studies using empirical data for evaluating the impact of forest related variables on sediment losses, most of them focusing on the impact of specific events, such as logging operations (Williams et al, 1995;Hartanto et al, 2003;Slesak et al, 2015) or recreational activities (Selkimäki & Mola-Yudego, 2011), and seldom on the impact of more general features such as forest structure and species composition (Selkimäki et al, 2012). Regarding gully erosion, it is recognized that forest has an impact on preventing or stabilizing gully erosion (Dotterweich et al, 2003;Rey, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, allocating stands of broadleaved trees (deciduous and evergreen) and short-needled conifer forest types has shown a remarkable impact in taming fire behaviour when a fire arrives from adjacent more flammable pine forest (Fernandes et al 2010). Finally, bush biomass control has revealed to be always a positive fire prevention strategy, especially when focussed on cleaning the transition zones between agricultural and forest land use, as some authors reported these areas to be prone to ignition (Gonzalez-Olabarria et al 2011;Martínez et al 2009), although taking into consideration the risk of erosion associated with vegetation modifications in arid Mediterranean areas (Selkimäki et al 2012). These areas could be considered as firebreaks, committing more resources for its maintenance and tightened up regulations for the use of fire.…”
Section: Discussionmentioning
confidence: 99%